FILANTROPI SEBAGAI PREDIKTOR NILAI PERUSAHAAN MELALUI KINERJA KEUANGAN - Suwandi Ng; Fransiskus Eduardus DAROMES; Merlin Lukita; Yakobus K Bangun; Lukman Lukman (Universitas Agung Podomoro, 2020)
This research demonstrates that philanthropic activity is a predictor of firm value through financial performance. The population used is all non-financial companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period. The number of samples is 101 companies each year, which were selected by purposive sampling method. The results of this study indicate that philanthropy has a significant effect on financial performance but not significant on firm value. However, another finding reveals that financial performance has a significant effect on firm value. Based on Sobel's test results, it shows that financial performance mediates the effect of philanthropy on firm value.